Modeling and Optimization of Feeder Bus Routes for Electric Train Service - CHONG, ANDY CHONG KONG KWONG (Universiti Teknologi Petronas, 2013)
This paper deals with the problem of unavailability and lack of efficiency and effectiveness of public transport that bring people to the Electric Train Service (ETS) station. The objectives of this project are to design a wide coverage feeder bus route that is also effective and efficient in terms of service. The scope of study of this project is to do research and literature review on optimization of feeder bus route as well as tomodel the optimal feeder bus route that has wide service coverage, lowest operation cost, shortest total travel time, shortest total travel distance and highest demand station for each of the ETS station. The hotspots aroundBatu Gajah have been identified. A few models of route optimization have been compared and the best model is implemented using MATLAB. Genetic Algorithm is used to solve theroute optimization problem by producinga wide coverage route with high effectiveness and efficiency in service.